Strategi Penataan Aktifitas Parkir dan Pedagang Kaki Lima pada Koridor Komersial Kota: Studi Kasus pada Koridor Jalan Gajah Mada, Sidoarjo - Mega Ayundya Widiastuti; Arfiani Syariah (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
The image characteristics of a city can be seen from it main streets corridor display. One of the aspects that affected the image was related to the parking spaces and street vendors arrangement. Gajah Mada street corridor as one of the main corridor in Sidoarjo City, its main activity was highly influenced by formal and informal commercial activities. Besides having a positive impact, the informal commercial sector also gave a negative impact for the corridor area.The Street vendors have occupied the sidewalk which had lead to pedestrian spatial activities transition up to the roadside. Those activities, along with inadequate parking space, have resulted in traffic congestion along the corridor. The study aimed to formulate the Gajah Mada Street corridor arrangement optimally for all of users convenience. The observations have shown that the traffic smoothness level along the Gajah Mada street varies on each zones.The corridor arrangement strategies was initiated through the parking location, type and time settings as well as the design of each business facilities. This research also has provided policy recommendation that can be taken by the local government related to parking arrangement and street vendors activities along the Gajah Mada street corridor of Sidoarjo.